2021
DOI: 10.20944/preprints202105.0064.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of cAMP and the Role of Epac2A During Activation, Activity, and Deactivation of Beta Cell Networks

Abstract: Beta cells couple stimulation by glucose with insulin secretion and impairments in this coupling play a central role in diabetes mellitus. To clarify the effect of cAMP and the role of Epac2A in intracellular calcium signals and intercellular coupling, we performed functional multicellular calcium imaging in beta cells in mouse pancreas tissue slices after stimulation with glucose and forskolin in wild-type and Epac2A knock-out mice. Increased cAMP evoked calcium signals in otherwise sub-stimulatory glucose an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 105 publications
3
5
0
Order By: Relevance
“…The results presented in Figure 3G,H indicate that increased levels of cAMP led to a denser and a more integral network (Figure 3H), thereby signifying a higher degree of synchronization between beta cells when compared to glucose stimulation only (Figure 3G). This is well in agreement with our previous results, where, in control experiments with prolonged glucose stimulation only, synchronized behavior diminished with time, but the activation of cAMP prevented this effect and enhanced the degree of beta cell synchronicity [199]. Most importantly, performing the same set of experiments with Epac2A KO mice, stimulation with forskolin restored the functional network integrity only partly.…”
Section: The Role Of Camp In Intercellular Couplingsupporting
confidence: 93%
See 1 more Smart Citation
“…The results presented in Figure 3G,H indicate that increased levels of cAMP led to a denser and a more integral network (Figure 3H), thereby signifying a higher degree of synchronization between beta cells when compared to glucose stimulation only (Figure 3G). This is well in agreement with our previous results, where, in control experiments with prolonged glucose stimulation only, synchronized behavior diminished with time, but the activation of cAMP prevented this effect and enhanced the degree of beta cell synchronicity [199]. Most importantly, performing the same set of experiments with Epac2A KO mice, stimulation with forskolin restored the functional network integrity only partly.…”
Section: The Role Of Camp In Intercellular Couplingsupporting
confidence: 93%
“…Finally, in our very recent study, we investigated explicitly how cAMP-mediated amplification affected the collective beta cell activity within the islets [199]. Our results showed that the activation of cAMP signaling did not only profoundly increase beta cell activity but also enhanced synchronicity and the coordination of intercellular signals.…”
Section: The Role Of Camp In Intercellular Couplingmentioning
confidence: 85%
“…Clearly, in the latter case, the network is characterized by more functional connections resulting in a more integral network, which indicates a higher degree of synchronization between beta cells. This is well in agreement with our previous results, where in control experiments with prolonged glucose stimulation only, synchronized behavior diminished with time, but the activation of cAMP prevented this effect and enhanced the degree of beta cell synchronicity [183]. Most importantly, performing the same set of experiments with Epac2A KO mice, stimulation with forskolin restored the functional network integrity only partly.…”
Section: The Role Of Camp In Intercellular Couplingsupporting
confidence: 93%
“…Finally, in our very recent study we investigated explicitly how cAMP-mediated amplification affected the collective beta cell activity within the islets [183]. Our results have shown that the activation of cAMP signaling did not only profoundly increase beta cell activity but also enhanced synchronicity and the coordination of intercellular signals.…”
Section: The Role Of Camp In Intercellular Couplingmentioning
confidence: 89%
“…Therefore, the influence of GLP-1RAs on beta cell activation and deactivation phases, which probably play a significant role during the first phase of insulin secretion and can help assess the risk of hypoglycaemia, respectively, remain to be explored (67)(68)(69). Additionally, modulation of [Ca 2+ ] IC dynamics by GLP-1RAs, particularly with respect to [Ca 2+ ] IC oscillation properties and functional connectivity during the plateau phase, are inadequately explored in the existing literature (70).…”
Section: Introductionmentioning
confidence: 99%